Defining, measuring, and enhancing resilience for small groups. (December 2019) - Zemba, Valerie; Wells, Emily M.; Wood, Matthew D.; Trump, Benjamin D.; Boyle, Bridget; Blue, Shala; Cato, Colanda; Linkov, Igor
Highlights: Literature review and meta-analysis on small team and unit resilience was performed. Focus on studies with trainings or interventions. Evaluated across four resilience phases: prepare, absorb, recover, adapt. Results suggest a focus on recovery, limited attention on absorption/adaptation. Abstract: Resilience is increasingly recognized as a factor that improves the functioning and performance of individuals and communities; however, it is underexamined in smaller groups or teams. We performed a comprehensive literature review to examine how resilience is defined, measured and used in small teams. Additionally, we evaluated the effectiveness of trainings or interventions on teams towards increasing unit resilience and performance. Following a literature review, 74 measures across 37 articles were assessed. Study eligibility criteria include English-language publications between 1980 and 2017 that included output from a research trial or survey on military or civilian groups pertaining to their resiliency to adverse events. Resilience of units/teams was assessed across the four phases of resilience defined by NAS: prepare, absorb, recover, adapt. Our review found that while the concept of resilience is not often studied in small groups empirically, the focus of available studies is on recovery with limited attention given to absorption and adaptation. This work reveals a potential mechanism to improve team/unit performance via unit resilience training and improved unit cohesion. Training had small but significant effects on the preparation ( r = 0.03, k = 5) and recover ( r = 0.05, k = 6) phases of unit resilience. In order to improve resilience in small groups, training programs and other interventions must be appropriately focused on the essential phases of resilience associated with mission execution.